International and foreign journals - De-Moya-Anegón, Félix (Anuario ThinkEPI, 2009)
The relationships between politics and scientists of interest in the findings of bibliometric studies are discussed in this text. The use of bibliometric arguments by commissions such as Cneai (Comisión Nacional de Evaluación de la Actividad Investigadora), among others, in the process of making decisions on "sections of research" and aspects of science policy, constitute a discussion of undoubted importance and interest to information professionals.
Keywords: Science policy; Research evaluation; Cneai; Bibliometrics.